Understanding the long-term trend of organic aerosol and the influences from anthropogenic emission and regional climate change in China - W. Zhang; Y. Liu; Y. Liu; M. Yue; M. Yue; X. Dong; X. Dong; X. Dong; K. Huang; K. Huang; K. Huang; M. Wang; et al. (Atmospheric Chemistry and Physics)
Organic aerosol (OA) is a major type of fine particulate matter. OA shows a large variability influenced by anthropogenic emissions, vegetation, and meteorological changes. Understanding OA trends is crucial for air quality and climate studies, yet changes in OA over time in China are poorly documented. This study applied the Community Atmosphere Model version 6 with comprehensive tropospheric and stratospheric chemistry (CAM6-Chem) to investigate long-term OA trends in China from 1990 to 2019 and identify the driving factors. The simulations agreed well with ground-based measurements of OA from 151 observational sites and the CAQRA reanalysis dataset. Although OA trends showed a modest 5.6 % increase, this resulted from a significant −8.1 % decrease in primary organic aerosols (POAs) and a substantial 32.3 % increase in secondary organic aerosols (SOAs). Anthropogenic emissions of POA and volatile organic compounds (VOCs) were the dominant contributors to these trends. While biogenic VOCs (BVOCs) played a secondary role in SOA formation, significant changes were observed in specific subspecies: isoprene-derived SOA decreased by −18.8 % due to anthropogenic sulfate reduction, while monoterpene-derived SOA increased by 12.3 % driven by enhanced emissions from rising temperatures. Through sensitivity experiments, our study found a negligible response of monoterpene-derived SOA to changes in anthropogenic nitrogen oxide (NOx) emissions as a net effect of changes in multiple pathways. This study highlights the complex interplay between POA reduction and SOA growth, revealing notable OA trends in China and the varying roles of both anthropogenic and biogenic emissions.